2018
DOI: 10.1007/s10705-018-9906-x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and nutrient use efficiency with integrated fertilization of buckwheat–fenugreek intercrops

Abstract: Intercrops and organic fertilizers can improve the productivity of cropping systems due to increased soil nutrient availability and plant nutrient use efficiency. A 2-year field experiment was conducted to determine the effects of different intercropping ratios and fertilizer types on nitrogen (N) and phosphorus (P) concentrations and yields of fenugreek and buckwheat at the research farm of Shahrekord University, Iran. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…The results are consistent with Chilimba et al (2014) who investigated agronomic biofortification in intercropped systems and observed a greater recovery of Se in maize-groundnut intercropped treatments compared to single cropped plots. Additionally, these findings may suggest improved 77 SeFert efficiency use when two or more crops are grown in association, as reported by Salehi et al (2018) for other plant nutrients (N). Thus, the reduced soluble and adsorbed 77 SeFert in the maize grown after cowpea and groundnuts rotation (T5C and T5G) plots is consistent with greater uptake of the applied 77 SeFert (Fig.…”
Section: Soluble and Adsorbed Sefertsupporting
confidence: 54%
“…The results are consistent with Chilimba et al (2014) who investigated agronomic biofortification in intercropped systems and observed a greater recovery of Se in maize-groundnut intercropped treatments compared to single cropped plots. Additionally, these findings may suggest improved 77 SeFert efficiency use when two or more crops are grown in association, as reported by Salehi et al (2018) for other plant nutrients (N). Thus, the reduced soluble and adsorbed 77 SeFert in the maize grown after cowpea and groundnuts rotation (T5C and T5G) plots is consistent with greater uptake of the applied 77 SeFert (Fig.…”
Section: Soluble and Adsorbed Sefertsupporting
confidence: 54%
“…Reagents and chemicals used in this study were acetonitrile HPLC grade (Chem-Lab NV, Belgium); FeCl 3 •6H 2 O, Folin-Ciocalteu reagent (Merck); AlCl 3 •6H 2 O, acetic acid p.a., TPTZ (2,4,6-tripyridyl-s-triazin, >99%) (Fluka); caffeic acid (>99%), HCl, ethanol (96%) p.a., isovitexin (ROTICHROM ® , >99%), vitexin (ROTICHROM ® , >99%), trigonelline hydrochloride >97.5%), methanol p.a., formic acid (ROTIPURAN, >98%), NaCH 3 COOH•3H 2 O, NaOH, NaNO 2 , and Na 2 CO 3 , were purchased from Roth; DPPH: 2,2-Diphenyl-1-Picrylhydrazyl (>99%), orientin (>97%), isoorientin (HPLC-grade, >98%), trolox: (±)-6-Hydroxy-2,5,7,8-tetra-methylchromane-2-carboxylic acid (>98%), and rutin (>99%), were obtained from Sigma-Aldrich. More detailed information on the sample preparation and analysis is provided in Salehi et al [15,16,27].…”
Section: Seed Analysis Reagents and Chemicalsmentioning
confidence: 99%
“…Overall, the application of BL and IF in intercropped systems increased the TC of the harvested fenugreek seeds. This can be explained by the availability of N due to the slower release of N from organic manure during the growing season and through additional soil N availability by the N-fixation of fenugreek [27]. Trigonelline is an alkaloid compound that is produced through methylation of nicotinic acid.…”
Section: Trigonelline Content (Tc)mentioning
confidence: 99%
“…[ 25,26 ] The seeds of fenugreek are widely used for their antidiabetic, anticarcinogenic, antioxidant, anticancer, hypocholesterolemic, and immunological properties. [ 27 ] Apart from medicinal benefits, fenugreek fixes atmospheric N, decreasing the N fertilizer need in cropping systems, [ 28 ] a characteristic of vital importance for low‐income farmers around the world. [ 29 ] Nitrogen fixing trait of fenugreek also makes it a feasible crop for intercropping with nonlegume crops, a common sustainable practice among small‐scale farmers in semiarid regions where plant production is limited by lack of water inputs, water retention, and low organic matter content.…”
Section: Introductionmentioning
confidence: 99%